TREATMENT OF PRESSURE ULCERS OF THE SCALP IN DECOMPENSATED HYDROCEPHALY: A CLINICAL CHALLENGE. - Letitia Bellavesta Kale; Elric Brahm Malelak; Robertus Arian Datusanantyo; Wajahat Ullah; Ahmed Mohamed Ahmed Ali; Dhyey Thumar; Kundan Kumar (Jurnal Rekonstruksi dan Estetik)
Highlights: